Evaluation of fringe projection and laser scanning for 3d reconstruction of dental pieces (2012)
The rapid prototyping and copying of real 3D objects play a key role in some industries. Both applications rely on the generation of appropriated computer aided manufacturing (CAM) files. These files represent a set of coordinates of an object and can be understood by a computer numerically controlled (CNC) machine. Non-contact techniques, like laser scanning and fringe projection, are among the possibilities for obtaining such CAM files. In this work, a comparison between the two aforementioned non-contact techniques is presented. The comparison is made based on their performance as candidates for generating CAM files of objects of high reflectivity and maximum lateral dimensions of the order of 15 mm The parameters tested are the quality of the 3D reconstruction, the processing time, and the possibility of these being implemented in industrial scenarios, among others. Under the scope of these parameters, it is concluded that laser scanning offers superior performance for the kind of objects here considered. The techniques are evaluated with dental pieces in order to validate these methodologies in the rapid prototyping and copying of teeth.